1993
DOI: 10.1073/pnas.90.23.11307
|View full text |Cite
|
Sign up to set email alerts
|

Direct gene transfer with DNA-liposome complexes in melanoma: expression, biologic activity, and lack of toxicity in humans.

Abstract: Direct gene transfer offers the potential to introduce DNA encoding therapeutic proteins to treat human disease. Previously, gene transfer in humans has been achieved by a cell-mediated ex vivo approach in which cells from the blood or tissue of patients are genetically modified in the laboratory and subsequently returned to the patient. To determine the feasibility and safety of directly transferring genes into humans, a clinical study was performed. The gene encoding a foreign major histocompatibility comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
342
0
4

Year Published

1998
1998
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 812 publications
(350 citation statements)
references
References 29 publications
4
342
0
4
Order By: Relevance
“…It was shown that DNA or DNA lipoplexes can mediate gene transfer into tissues and facilitate gene expression locally at higher concentrations. 17,18,28 The expression of IFNs can, in the case of BCC, be achieved locally and may help to avoid systemic effects. Because these studies were performed in immunodeficient recipients, the mechanism was presumably nonimmune.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that DNA or DNA lipoplexes can mediate gene transfer into tissues and facilitate gene expression locally at higher concentrations. 17,18,28 The expression of IFNs can, in the case of BCC, be achieved locally and may help to avoid systemic effects. Because these studies were performed in immunodeficient recipients, the mechanism was presumably nonimmune.…”
Section: Discussionmentioning
confidence: 99%
“…Nonviral gene delivery, and subsequent uptake by cells in vivo, has been described and proven to be a valid methodological approach. 17,18 The advantage of a nonviral gene transfer is that the different components are stored stably for long periods of time and do not represent a significant biological hazard. This approach can potentially also be applied to other skin diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cationic liposomes are the most commonly used nonviral delivery system for delivery of plasmids into cells in vitro [1][2][3] and in vivo. [4][5][6] A significant problem associated with cationic liposomes is their low in vivo transfection efficiency, 7,8 possibly due to inactivation of the liposomes by serum. 9,10 Despite this limitation, cationic liposome carriers have several major advantages such as relative ease of large-scale production and minimal toxicity.…”
Section: Introductionmentioning
confidence: 99%